The Effect Of Social Contacts On The Spreads Of Covid-19 In Indonesia - Fadilah, Mariatul; Arsinta, Dewi (Advances in Social Sciences Research Journal, 2020)
Introduction: Covid-19 is an infectious disease. Matrix that is often used to identify transmission of infectious diseases dynamics is Basic Reproduction Number (R0). R0 is influenced by 3 parameters there are transmissibility (τ), average contact (c) and duration of infectiousness (d). Transmissibility and duration of infectiousness are constant values. The value of R0 will fluctuate if the rate of human interaction varies. The value of social contact different in every country. In Indonesia, there are no studies that discuss the value of social contact. Therefore researchers aims to find out these values and determine their effect on the spread of Covid-19. Method: This research was a descriptive observational study. Aims of the study is evaluate the pattern of social contact associated with the spread of covid-19. Data was collected using POLYMOD questionnaire that distributed via google form. The research sample was Indonesian people who were reached by distributing questionnaires. The data obtained then analyzed using the SPSS program to find the frequency distribution, mean of social contact and logistic regression analysis. Results: From this study, 6464 contacts were obtained from 1032 respondents with average number of contacts 6.26 and R0 2.191. Conclusion: The higher of contact value the higher risk of transmission. The R0 value obtained is 2.191, so one infected person might be able to transmit it to two other people around them. Individuals who are most at risk for transmission is male with low education levels and students.